Human pathogenic Mycobacterium kansasii (former subtype I) with zoonotic potential isolated from a diseased indoor pet cat, Japan - Hanako Fukano; Tsukasa Terazono; Aki Hirabayashi; Mitsunori Yoshida; Masato Suzuki; Shinpei Wada; Norihisa Ishii; Yoshihiko Hoshino (Emerging Microbes and Infections)
Nontuberculous mycobacterial (NTM) infections in humans have increased in prevalence in recent decades. Mycobacterium kansasii is one of the most prevalent human pathogenic NTM species worldwide. Herein, we report the first isolation of M. kansasii from an indoor domestic cat in Japan. Comparative genome sequence analysis of the feline isolate showed this pathogen is genetically identical to human pathogenic M. kansasii.This finding suggests that M. kansasii has a potential risk of zoonoses and requires the “One Health” approach to control NTM infection.